Persistence of use of prescribed cannabinoid medicines in Manitoba, Canada: a population‐based cohort study. (19th July 2019) - Alkabbani, Wajd; Marrie, Ruth Ann; Bugden, Shawn; Alessi‐Severini, Silvia; Bolton, James M.; Daeninck, Paul; Leong, Christine
Abstract: Background and aims: To estimate prevalence of continuous use (persistence) of prescribed cannabinoid medications for up to 1 year from initial prescription in Manitoba, Canada and predictors of duration of use. Design and setting: A retrospective, population‐based, cohort study using administrative data from the Manitoba Population Research Data Repository located at the Manitoba Centre for Health Policy, Canada. Participants: People without a record of a previous prescription who were prescribed a cannabinoid medication from 1 April 2004 to 1 April 2016 followed for 1 year from the date of first prescription. Measurements: Continuous prescribed cannabinoid medication use was defined as use without a gap exceeding 60 days between prescriptions. The primary outcome was prevalence of continuous prescribed cannabinoid medication use for up to 1 year. A secondary outcome was duration of continuous use. Predictors were socio‐demographic characteristics, medical diagnoses and type of cannabinoid medication. Findings: Among 5452 new users, 18.1% [95% confidence interval (CI) = 17.08–19.12] were still using cannabinoids at 1 year. Median duration of use was 31 days [interquartile range (IQR) = 25–193]. This was highest for nabilone (33 days, IQR = 25–199) and lowest for nabiximols (20 days, IQR = 7–30). Use was longest among 19–45‐ and 46–64‐year‐old users and those with the highest socio‐economic status. Fibromyalgia [hazard ratio (HR) = 0.89, 95% CI = 0.84–0.95], osteoarthritis (HR = 0.91, 95% CI = 0.82–0.97) and substance use disorder (HR = 0.85, 95% CI = 0.76–0.94) diagnoses were associated with longer use (HR for discontinuation—HR < 1 less discontinuation and longer use). A diagnosis of cancer was associated with shorter use (HR = 2.73, 95% CI = 2.02–3.67). Conclusions: In Manitoba, Canada approximately 18% of people prescribed cannabinoid medication continue using for at least 1 year. Duration of use varies with type of cannabinoid medication, age, socio‐economic status and dagnosis.